Effects of low-carbohydrate, high-nutrient-density diet combined with aerobic exercise on mental health and glycolipid metabolism in obese children and adolescents - Li, Long; Zhang, Peiwen; Liu, Xingyu; Wang, Chun (Frontiers in Medicine, 2026)
ObjectiveTo explore the effects of low-carbohydrate, high-nutrient-density diet combined with aerobic exercise on mental health and glycolipid metabolism in children and adolescents with obesity.MethodsA total of 121 children and adolescents with obesity treated in our hospital from January 2022 to December 2023 were enrolled in this study and divided into a control group (n = 60) and a study group (n = 61). The control group received balanced diet, lifestyle, and exercise education. The study group adopted a low-carbohydrate and high-nutrient-density diet, restricting carbohydrate intake while emphasizing foods rich in essential nutrients like vitamins and minerals, combined with daily aerobic exercise (swimming, jogging, skipping, and badminton, running, or climbing stairs, 30–60 min per session). The intervention lasted for 8 weeks. The body fat metabolism, blood lipid parameters, blood glucose related indexes, psychological status, and quality of life, were compared in the two groups.ResultsAfter intervention, body mass index (BMI), body fat content, body fat percentage, and waist-to-hip ratio were lower in the study group [(17.56 ± 1.72) kg/m2, (17.41 ± 1.75) kg, (38.01 ± 3.82) %, and (0.72 ± 0.07)] compared with the control group [(19.32 ± 2.01) kg/m2, (19.02 ± 1.95) kg, (41.78 ± 4.18) %, and (0.89 ± 0.09)] (p < 0.05). After intervention, the study group exhibited lower improvements in total cholesterol (TC) and low-density lipoprotein (LDL-C) and more favorable triglyceride (TG) and high-density lipoprotein (HDL-C) [(4.06 ± 0.41) mmol/L, (4.26 ± 0.43) mmol/L, (1.16 ± 0.12) mmol/L, and (1.65 ± 0.17) mmol/L] compared with the control group [(5.91 ± 0.60) mmol/L, (3.65 ± 0.36) mmol/L, (1.62 ± 0.16) mmol/L, and (1.38 ± 0.14) mmol/L] (p < 0.05). After intervention, the levels of fasting blood glucose (FPG), C-peptide (C-P), fasting insulin (FINS), and homeostasis model islet resistance index (HOMA-IR) were lower in the study group [(4.82 ± 0.48) mmol/L, (5.18 ± 0.52) μU/mL, (539.65 ± 53.24) pmol/L, and (1.12 ± 0.11)] when compared with the control group [(5.45 ± 0.55) mmol/L, (8.62 ± 0.86) μU/mL, (723.15 ± 72.35) pmol/L, and (1.92 ± 0.19)] (p < 0.05). After intervention, the self-rating anxiety scale (SAS) and self-rating depression scale (SDS) scores were lower in the study group [(36.28 ± 3.62) points and (37.26 ± 2.71) points] when compared with the control group [(42.23 ± 4.23) points and (43.82 ± 4.38) points] (p < 0.05). After intervention, the scores of social, psychological, physical, and emotional function were higher in the study group [(86.65 ± 8.21) points, (83.54 ± 8.35) points, (85.62 ± 8.46) points, and (86.21 ± 8.61) points] than those in the control group [(80.23 ± 8.01) points, (78.21 ± 7.82) points, (80.32 ± 8.14) points, and (80.15 ± 8.06) points] (p < 0.05).ConclusionLow-carbohydrate and high-nutrient-density diet combined with aerobic exercise significantly improves mental health and glycolipid metabolism in children and adolescents with obesity.